The use of the oral history teaching approach in social studies towards strengthening national values and identity among Kuwaiti youth: a consideration of Kuwait Vision 2035 - Al-Shammari, Abdulaziz K (Kansas State University, 2021)
The study examined three factors in order to demonstrate and prove the effectiveness of implementing oral history in teaching social studies: teachers’ perceptions, teachers’ familiarity, and oral history’s effectiveness as a teaching approach. The goal of the study was to answer the following research questions: (1) what are the perceptions of middle-school social studies teachers concerning the use of oral history as a teaching approach, (2) how familiar are social studies teachers with the oral history-based approach, and to what extent is it incorporated into their teaching, and (3) how effective is using an oral history-based approach in social studies to improve Kuwaiti students’ national values and identity? Purposeful sampling was used in the selection of participants. This included focus group discussion, interviews, survey questionnaires, and observation notes, which were used for data collection. Thematic analysis was used to analyze the data after it was gathered. The findings were categorized into three themes; (a) perceptions of middle-school social studies teachers concerning the use of oral history as a teaching approach, (b) familiarity of social studies teachers using oral history as a teaching approach, which included the extent of its integration into their teaching, and (c) effectiveness of teaching social studies using an oral history approach to improve Kuwaiti students’ national values and identity. The implications may be applied to a wide range of professional approaches as well as practical applications appealing to a variety of aspects, but in particular to the educational setting. The most noteworthy finding of this research study was the need to integrate the oral history approach at the institutional level in order to jump-start the approach’s implementation within classrooms. Social studies teachers perceived oral history as an effective teaching approach for multiple reasons. The first reason was due to its ability to create high engagement within the classroom, increasing students’ responses. Another reason was it was viewed as an efficient tool for personal and intellectual development among students. It was also viewed as a supplementary learning material and a useful research tool in class. In addition, it was an effective social tool for improving students’ national values and identity by increasing awareness. It was a critical part of the learning environment. A number of recommendations for further studies have been forwarded in the hopes of applying these to effectively and continuously use the oral history-based approach in the classroom; the educational institutions, as well as the state, should spare no effort in the production of resources and materials in order to support teachers. Providing skills, training, and seminars should be considered in order to elevate and promote oral history-based approach within classrooms.
Keywords: Oral history approach; Social studies; National values; National identity; Teaching method; Social studies teachers